Modeling for energy optimization in wetland paddy production in North-West Selangor, Malaysia - Muazu, Aliyu (2015)
In Malaysia, rice is the staple food for the populace and a source of income to the majority of the rural dwellers. The country relies on imported rice to argument the shortfall in local production vis-à-vis demand. The locally produced rice cost more than similar grade of imported rice. Reducing production cost and enhancing paddy productivity are achieved through optimum use of resources, to which on-farm energy analysis plays a central role by addressing issues of excess energy use. In this study, a thorough on-farm evaluation of farm inputs and output was conducted in 40 farms with net cultivation land area of 27.005 ha at Block E5 Parit Lima Timur, Sungai Besar, North-West Integrated Agricultural Development Authority Selangor, to determine energy and cost efficiency of paddy production in the area and to develop a computer-based platform for appraising performance. The measured farm inputs were converted into energy values using appropriate conversion coefficients and the cost of inputs evaluated based on the prevailing market rate. The technical efficiency of the farms was determined using input oriented constant return to scale Data nvelopment Analysis (DEA) methodology. Quantification of excess energy used in the farms was done using DEA identified benchmarks. The benchmarking results were used to develop maximum yield predictive models for performance appraisal. A method of reference frequency was used to determine best paddy cultivation practices for enhanced paddy productivity. A motion study was conducted to evaluate the mechanization indexes of operations and in the development of fuel predictive models. From the results of the study, at mean yield of 7625 kg/ha, the energy expenditure was 16,440 MJ/ha with energy intensity value of 2.16 MJ/kg. Cost-wise farmers in the study area expended about RM6658/ha and had a benefit-cost ratio of 1.37 and 1.68 with and without government subsidy respectively.